Validity of global positioning system technology to measure maximum velocity sprinting in elite sprinters - Thome, M.; Thorpe, R. T.; Jordan, M. J.; Nimphius, S. (The Journal of Strength and Conditioning Research, 2023)
The objective of this study was to assess the concurrent validity of 10-Hz wearable Global Positioning System (GPS) technology to measure maximum velocity sprinting (Vmax) relative to Doppler radar in elite sprinters. Data were collected from a single training session performed by elite 100 and 200 m sprinters (males: n = 5; 100 m best times: 10.02 ± 0.07 seconds, range: 9.94-10.10 seconds; 200 m best times: 20.29 ± 0.42 seconds, range: 19.85-20.80 seconds; females: n = 2; age: 28.0 ± 4.2 years; body mass: 65.8 ± 4.6 kg; 100 m best times: 11.18 ± 0.34 seconds; 200 m best times: 22.53 ± 0.04 seconds). Velocity and time data from 16 maximal, 60-m sprint efforts were recorded simultaneously with 10 Hz GPS and 47 Hz radar. Validity was assessed using Bland-Altman 95% limits of agreement (LOA) and intraclass correlation coefficient (ICC), each with respective 95% confidence intervals (CI). Vmax measured with 10 Hz GPS demonstrated a LOA of -0.11 m·s-1 (-0.17, -0.05) and an ICC of 0.99 (0.98, 1.0) relative to the radar device.10 Hz GPS overestimated Vmax by 0.11 m·s-1 relative to the radar but could still be considered a suitable tool for monitoring external load in elite sprinters. However, the much smaller average annual improvement in this population (~0.1-0.2%) in comparison with the ~1% overestimation reduces the utility of 10 Hz GPS to detect meaningful performance changes in maximum velocity.